Accumulation of Heavy Metals Lead (Pb) and Copper (Cu) in Mangrove Area of Avicennia marina in Manyar Subdistrict, Gresik District, East Java - Made Dwipa Kusuma Maharani; Asus Maizar Suryanto Hertika; Muhammad Musa (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Brawijaya, 2019)
Human and industrial activities in the area of Manyar Subdistrict Mangrove Waters, Gresik District can increase pollution and the presence of heavy metals in aquatic environments and aquatic organisms. This triggers input of heavy metals, especially Pb and Cu. Mangroves can accumulate and have a high tolerance for heavy metals so they can be used as plants for phytoremidiation purposes (phytostabilization). The mangrove ecosystem can be used as a control of heavy metal pollution and can also be used as a pollutant trap. This study was conducted to determine the potential of phytoremidiation based on the accumulation and translocation of heavy metals in Avicennia marina mangroves in absorbing heavy metals Pb and Cu from their environment. Based on research results MacFarlane et al., (2007) mangrove Avicennia marina is one of the plants that can effectively accumulate heavy metals due to its root system. The sample was analyzed using AAS (Atomic Absorption Spectrophotometer). The research parameters include levels of Pb and Cu metals in sediments, mangrove roots and leaves. The results of Pb heavy metal concentrations ranged from 0.30 ppm - 4.84 ppm and Cu ranged from 0.27 ppm - 11.42 ppm with the highest values found in sediment stations 2. Avicennia marina at the study site was excluder because the BCF value < 1 which ranged from 0.02 - 0.18 ppm and phyto-extraction because the value of TF > 1 ranged from 0.35 to 1.69 ppm. The results of this study indicate that Avicennia marina mangroves can be developed into phytoremidiation agents because they are able to absorb and transfer heavy metals from the environment to other body tissues.